Between Flogging and Imprisonment: The Disparity Effect of the Sharia Court's Decision on the Supremacy of the Qanun Jinayat of Aceh - Salma, Salma; Rama, Alfi Syukri; Jarudin, Jarudin; Samsudin, Muhammad Adib bin; Fadhilah, Defi Rahmi (Institut Agama Islam Negeri Curup, 2024)
This research aims to map the same cases with different sentencing decisions, determine the causes for the disparities in penalties in those decisions, and elaborate on the reasons for judges in making decisions. Qanun Jinayat of Aceh has designated flogging as the primary punishment for qanun violators. Nonetheless, many Sharia Court judges sentence offenders of sexual crimes to prison. This is empirical legal research with a normative juridical approach and a Sharia approach. Data were collected through interviews and the examination of decision documents. Those data were analyzed using data reduction, data display, and data verification. This research found that the same cases with different decisions include cases of rape, sexual harassment, and accusations of adultery. More prison sentences are imposed by Sharia Court judges in these cases than flogging and fines. The fundamental reason for these differences in decisions is due to the qanun's punishment choices, which are tinted by judges' perspectives in assessing Sharia-based qanun rules. Another factor for this disparity is the community's insistence that cases of rape and sexual harassment be punished by imprisonment or the authority to be remanded to the District Court. Some people argue that flogging has not deterred the perpetrators because, if the judge decides on this sentence, it may be carried out in a short time. Then, the perpetrator immediately returns to society and has an opportunity to repeat his crimes, while the victim is still in a traumatized state.